ACTION RESEARCH IN EDUCATION - Jonida Lesha (European Scientific Journal, ESJ, 2014)
Action Research is a formative study of progress commonly practiced by teachers in schools. Basically an action research is a spiral process that includes problem investigation, taking action & fact-finding about the result of action. It enables a teacher to adopt/craft most appropriate strategy within its own teaching environment. Action research is actually suitable for any person who wishes to improve his or her performance; or any group or organization who hopes for doing the same. As a matter of fact, action research is widely used in education, especially by teachers who use it to improve their teaching. Teachers from all over the world have employed action research as a part of their teaching and research. Obviously, action research well matches with education and benefits both teachers and students in their teaching and learning since it meets the need of education and enables continuity in research with its cyclic process. The suitability of action research to education reveals in its nature, characteristics, “circle within circle” process, etc. This article will look at all aspects concerning action research including definitions, advantages, steps, etc to see the importance and the benefits of action research to education.